EVALUATION OF THE IMPLEMENTATION OF THE PROJECT-BASED LEARNING (PJBL) PROGRAM BASED ON SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEAM) - AMALIA, Stevy (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
This research aims to find, reveal, and analyze the success of the implementation of the STEAM-based PjBL program. This research is evaluative by evaluating the implementation of STEAM-based PjBL at Putri Mazaya Assunnah Middle School to improve students' conceptual and critical thinking skills. The evaluation model used is a qualitative approach using the Countenance Evaluation Model developed by Robert Stake, including the background context of the program, the program implementation process, and the output of program implementation achievements. Participants in this research included school principals, teachers, and students. Observations, interviews, and documentation were used to collect research data. Data validity with source triangulation. Evaluation findings: first, in the context of the background and implementation objectives, it is by the vision, mission, and objectives through the implementation of the implemented curriculum. Second, in the program implementation process, there needs to be an evaluation of the STEAM-based PjBL implementation time analysis and consistency in carrying out monitoring activities during program implementation. Third, the output from the implementation of the STEAM-based PjBL program can make it easier for students to achieve learning goals. In facing challenges and obstacles, it is necessary to reflect and evaluate with all teachers to facilitate the preparation of follow- up plans for the STEAM-based PjBL program. The implications of the research results need to be reviewed regarding the technical aspects of preparing program implementation plans and analyzing the implementation time for project completion.